(untitled) (Research, Society and Development, 2024)
This is a descriptive study, of the data collection type, conducted through the survey of bibliographic data in the year 2024. The present study highlights aspects of the kangaroo method and its benefits for neonatal care, as well as the role of nursing in the implementation and promotion of the method. Therefore, the aim is to discuss the impact of the kangaroo method on the lives of newborns and their families from the nurse’s perspective. Thus, the study allowed for describing and providing a comprehensive view on the themes of nursing care related to the Kangaroo Method, with humanization as the focus of care in the assistance of newborns based on scientific literature. Nursing care plays a crucial role in the application of the Kangaroo Method, in its development, safety, self-efficacy, contributing positively in partnership with the multidisciplinary team, newborns, and families.